Integration Processes in the System of Lifelong Education at the Comrat State University - Serghei Zaharia; Oxana CURTEVA (ACROSS)
Integration processes as a response to the challenges of modern society manifest themselves in different forms and at different levels of the education system. Leading EU countries successfully integrate life-long learning into the adult education system and strive to ensure the mass participation of the adult population in training programs. Realizing the idea of lifelong learning, the Center for Continuing Education has been successfully functioning at the Comrat State University. The international project COMPASS - TOWARDS EUROPEAN UNIVERSITY LIFE LONG LEARNING MODEL IN MOLDOVA is aimed at integration into the university model of lifelong learning. COMPASS is a progressive project that greatly expands the opportunities to organize the process of continuous education for specialists.